Safety of xylo-oligosaccharides (XOS) as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA); Turck D; Bresson J-L; Burlingame B; Dean T; Fairweather-Tait S; Heinonen M; Hirsch-Ernst KI; Mangelsdorf I; McArdle HJ; Naska A; Neuhäuser-Berthold M; et al. (John Wiley and Sons Ltd on behalf of European Food Safety Authority, 2018)
Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on a mixture of xylo-oligosaccharides (XOS) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is obtained from corncobs (Zea mays subsp. mays) via enzyme-catalysed hydrolysis and subsequent purification. The main components of the NF, the oligosaccharides, are resistant to human digestive enzymes and are fermented by colonic bacteria. The intention is to add the NF to a variety of foods such as bakery and dairy products, fruit jelly, chocolates and soy-drinks. The information provided on composition, specifications, production process and stability of the NF, does not raise safety concerns. There were effects observed in the animal studies with the NF or with other XOS which were considered by the Panel to be expected from the intake of non-digestible carbohydrates. The Panel notes that the acute and transient gastrointestinal observed in human intervention studies with the NF or with other XOS have also been associated with the consumption of other non-digestible carbohydrates. The Panel concludes that the NF, a mixture of XOS, is safe under the proposed uses and use levels. The target population is the general population.
Keywords: xylo-oligosaccharides; XOS; novel food; safety